Enucleation: a treatment alternative for branch duct intraductal papillary mucinous neoplasms - Kaiser, Jörg; Fritz, Stefan; Klauß, Miriam; Bergmann, Frank; Hinz, Ulf; Strobel, Oliver; Schneider, Lutz; Büchler, Markus W.; Hackert, Thilo (Surgery, 2017)
Background: Small, asymptomatic, branch-duct intraductal papillary mucinous neoplasms of the pancreas are often kept under surveillance despite their malignant potential. The management of branch-duct intraductal papillary mucinous neoplasm is controversial with regard to indications and extent of any operative intervention. The present study aimed to evaluate enucleation as an alternative operative approach for branch-duct intraductal papillary mucinous neoplasms to exclude and prevent malignancy. Methods: For branch-duct intraductal papillary mucinous neoplasms of <30 mm in diameter and an acceptable distance from the main pancreatic duct, enucleation was considered as the operative approach of choice. All patients scheduled for enucleation of branch-duct intraductal papillary mucinous neoplasm on the basis of these features between January 2004 and September 2014 were analyzed. Among these, patients with successful enucleation were compared with those who were scheduled for enucleation but converted intraoperatively to pancreatic resection (intention-to-treat analysis). End points were hospital morbidity and mortality as well as histopathology and functional outcome at a mean follow-up of 32 months.Results: In the study, 115 patients with presumed branch-duct intraductal papillary mucinous neoplasm and the intention to perform pancreatic enucleation were included; 87 enucleations were performed in 74 patients. In 41 patients, enucleation was converted to a pancreatic resection (procedure-specific success rate 64%); indications for conversion included location or size (46%), presence of multicystic lesions (39%), or involvement of the main pancreatic duct (15%). Of the 74 patients with enucleation, 64 branch-duct intraductal papillary mucinous neoplasms revealed low- (85%), 11% moderate dysplasia-, and 4% high-grade dysplasia on histology. Among converted resections, 6 intraductal papillary mucinous neoplasms revealed high-grade dysplasia or invasive carcinoma (15%). Intention-to-treat analysis with patients converted to pancreatic resection showed that enucleations resulted in less blood loss (100 vs 400 mL) and a shorter operation time (146 vs 255 minutes; P < .001 each). Postoperative morbidity including postoperative pancreatic fistula was similar in both groups. No mortality occurred after enucleation; after formal resection, 1 patient died due to multiorgan failure. Both hospital stay (10 vs 14 days) and rates of postoperative endocrine and exocrine dysfunction rates were less after enucleation (P < .02 each). Intraductal papillary mucinous neoplasm-specific recurrence rates (3% vs 6%) were similar in both groups. Conclusion: Enucleation is a safe procedure that can be performed successfully in a high proportion of branch-duct intraductal papillary mucinous neoplasms and should be considered instead of standard resections as an important function-preserving alternative. Limitations may occur due to malignancy, size, localization, multilocularity, or main-duct involvement requiring conversion to a formal, anatomic resection. Beside the advantages in the short-term course, functional outcome seems to be superior after enucleation, and intraductal papillary mucinous neoplasm-specific recurrence rates are not increased compared with standard resections, at least at a mean follow-up of 32 months.